Pengaruh Lama Perendaman dan Konsentrasi Asam Sulfat (H2SO4) terhadap Perkecambahan Benih Jati (Tectona grandis Linn.f) - Suyatmi, Suyatmi; Hastuti, Endah Dwi; Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The Aims of the research to determine the effect of soaking time and concentration of H2SO4 on the germination of seeds jati (Tectona grandis Linn. f). The research using a Completely Randomized Design (CRD) with factorial pattern Â 3 x 4. Factor I is a long time soaking (W1: 20 minutes, W2: 30 minutes and W3: 40 minutes), factor II is the concentration of H2SO4 (K0: 0%, K1: 70%, K2: 80% and Â Â K3: 90%). Each treatment with three replications. The data obtained were analyzed by ANAVA at 95% significance level, followed by Duncan's test at the 95% test level. Parameters observed were: the percentage of germination (%),hipokotil seedling length (cm), radicels seedling length (cm) and seedling dry weight (gr). The results showed there were interactions between treatment long time soaking and H2SO4 concentration on the percentage of seed germination of jati. Interaction treatment 70% H2SO4 concentration on the length of soaking of 30 and 40 minutes showed the highest percentage germination. Seeds that capable to germinate under thus treatment the seedling growth is not affected by treatment.